AN ONLINE VIRTUAL EDUCATIONAL CENTER - Gardiyawasam, Tharindu; Dias, G.K.A. (International Journal of Research -GRANTHAALAYAH, 2017)
During the past decade, Sri Lankan education system has transformed in to a highly competitive level and as a result private tuition has now become a necessity in Sri Lankan society. One main concern for most students when selecting a tuition class is the physical distance to the class from their home. As a result, most students have to waste a lot of time and money just for travel to the class. Although Individual and small/group classes provide a customized service compared to open classes, students have to bear a considerably higher tuition fee and that could prevent most students from getting such a service from teachers. Also most teachers have to address the issue of limited space availability and as a result they have to either rent a place or have to limit the number of students to fit in to the available limited space. This web based system enables both students and teachers to self-register in the system and engage in all the typical class room activities with the use of internet. Teachers will be able to conduct live online classes via the system and large number of students will be able to participate classes from their residences. Also various educational resources are available in the system which enables everyone to be fully interacted with each other. Additionally functionalities to generate administrative reports, track visitor details and user activities are also included in the system along with more other useful functionalities. Students will get a customized service and limited space will no longer be a problem for teachers as everyone will interact based on their own locations. So this system will provide a cheaper way of conducting classes than current tuition classes, and also it is expected to operate as a way of minimizing the issues of the current private tuition education sector. Currently the system is based on English language and supports only one local language ‘Sinhala’.